Choline phosphate cytidylyltransferase‐α is a novel antigen detected by the anti‐ERCC1 antibody 8F1 with biomarker value in patients with lung and head and neck squamous cell carcinomas. Issue 12 (1st April 2014) - Vaezi, Alec E.; Bepler, Gerold; Bhagwat, Nikhil R.; Malysa, Agnes; Rubatt, Jennifer M.; Chen, Wei; Hood, Brian L.; Conrads, Thomas P.; Wang, Lin; Kemp, Carolyn E.; Niedernhofer, Laura J.
Abstract : BACKGROUND: The determination of in situ protein levels of ERCC1 with the 8F1 monoclonal antibody is prognostic of survival in patients with non‐small cell lung cancer (NSCLC). The authors previously demonstrated that 8F1 recognizes a second nuclear antigen. This antigen was identified and its value as a biomarker of clinical outcomes analyzed. METHODS: The second antigen was identified by mass spectrometry. Protein identity and antibody specificity were confirmed through knockdown and overexpression experiments. Immunohistochemistry of 187 early‐stage NSCLC samples and 60 head and neck squamous cell carcinomas (HNSCCs) was used to examine the influence of the second antigen on 8F1 immunoreactivity and its association with patient outcomes. RESULTS: Choline phosphate cytidylyltransferase‐α (CCTα, also known as phosphate cytidylyltransferase 1 choline alpha [PCYT1A], a phospholipid synthesis enzyme regulated by RAS) is the second antigen recognized by 8F1. In NSCLC samples, CCTα contributed (rho, 0.38) to 8F1 immunoreactivity. In samples of squamous cell carcinomas of the lung, CCTα was found to be the dominant determinant of 8F1 immunoreactivity, whereas its contribution in other subtypes of lung cancer was negligible. High expression of CCTα, but not ERCC1, was found to be prognostic of longer disease‐free survival (log‐rank P  = .002) and overall survival (log‐rank P  = .056). Similarly, in patients with HNSCC, CCTα contributed strongly to 8F1 immunoreactivity (rho, 0.74), and high CCTα expression was found to be prognostic of survival (log‐rank P  = .022 for disease‐free survival and P  = .027 for overall survival). CONCLUSIONS: CCTα is the second antigen detected by 8F1. High CCTα expression appears to be prognostic of survival in patients with NSCLC who are treated by surgery alone and patients with HNSCC. CCTα is a promising biomarker of patient survival and deserves further study. Cancer 2014;120:1898–1907 . © 2014 American Cancer Society . Abstract : The monoclonal antibody 8F1 has been used to determine ERCC1 levels to predict platinum efficacy and as a prognostic marker for the survival of patients with malignancies. The results of the current study demonstrate that 8F1 detects 2 unrelated proteins, ERCC1 and choline phosphate cytidylyltransferase‐α (CCTα), and that CCTα is prognostic for survival in patients with lung and head and neck squamous cell carcinomas.